Controllable synthesis of polydopamine nanoparticles in microemulsions with pH-activatable properties for cancer detection and treatment1. Issue 33 (7th September 2015) - Liu, Fuyao; He, Xiuxia; Zhang, Junping; Chen, Hongda; Zhang, Huimao; Wang, Zhenxin
<x xml:space="preserve">Abstract</x> A simple reverse microemulsion-based method was used to elaborate pH-activatable PEG–Fe–PDA nanoparticles for cancer diagnosis and therapy.